Avaliação da Disfunção Temporomandibular (DTM) e dor orofacial associadas a hábitos parafuncionais e fatores psicológicos em acadêmicos da Polícia Militar - Cavalcanti, Maria Oliveira Alves (2009)
This study aimed to estimate the incidence of temporomandibular disorders (TMD) and orofacial pain, its severity and the presence of habits and psychological factors in a population of non-patients represented by students of the Military Police Academy. Methodology was a cross-sectional study with an inductive approach and technique of extensive direct observation using a questionnaire. The sample was composed of students of both genders, enrolled in the Academy of Military Police of the Cabo Branco, based in the Education Center of Military Police in João Pessoa, Paraíba. It was evaluated the sample characterization variables (gender, age, marital status), TMD degree classification and the TMD history index of Fonseca on habits and psychological factors involved in using the questionnaire of the Research Diagnostic Criteria for TMD (RDC / TMD) Axis II. The level of significance used in statistical tests was 5% and the intervals were obtained with 95% confidence. The sample consisted of 148 participants aged 18 to 36 years, mostly male (77.7%). We observed the presence of TMD in 49.3% of respondents, with a higher prevalence in females and of mild TMD. It was found that among respondents who had TMD, the more significant parafunctional habit was the gnashing of teeth (89.5%), demonstrating an association between TMD and the habits of gnashing teeth, tighten the teeth and biting objects. Statistically significant association (p <0.05) was also found between TMD and all the signs and symptoms, except for jaw lock. Pain in the orofacial region was found in 18.9% of the participants, and in most individuals, it was cronic. Psychological factors such as depression, somatization with pain and somatization without pain were significantly associated with TMD, showing that in subjects with higher levels of depression and somatization in TMD is expressed more intensely. The TMD was present in about half the population under study, with proven association between it and the deleterious habits examined, as well as with psychological factors like depression, somatization with pain and without pain, emphasizing even a correlation between the severity of TMD and psychological factors.